Combining Fuzzy AHP with GIS and Decision Rules for Industrial Site Selection - Taibi, Aissa; Atmani, Baghdad (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
This study combines Fuzzy Analytic Hierarchy Process (FAHP), Geographic Information System (GIS) and Decision rules to provide decision makers with a ranking model for industrial sites in Algeria. A ranking of the suitable industrial areas is a crucial multi-criteria decision problem based on socio-economical and technical criteria as on environmental considerations. Fuzzy AHP is used for assessment of the candidate industrial sites by combining fuzzy set theory and analytic hierarchy process (AHP). The decision rule base serves as a filter that performs criteria pre-treatment involving a reduction of their numbers. GIS is used to overlay, generate criteria maps and for visualizing ranked zones on the map. The rank of a zone so obtained is an index that guides decision-makers to the best utilization of the zone in future.
Keywords: Geographic information system; multi-criteria decision analysis; industrial site selection; fuzzy analytic hierarchy process; decision rules; IJIMAI